Determinants of Labor Force Participation of Female Ketak Wickerworkers in Saribaye Village, Lingsar Subdistrict, Lombok Barat Regency - Widya Saptafitri Audina; Taufiq Chaidir; Gusti Ayu Arini (Tinta Emas Institute, 2023)
This research aims to analyze wages, work experience, age, number of dependents, marital status and the presence of toddlers as determinants that influence the labor force participation of women ketak woven craftsmen in Saribaye village, Lingsar sub-district, West Lombok district. This type of research is explanatory quantitative. The data in this research is primary data with data collection methods using the census method. The population in this study were 40 female ketak woven craftsmen in Saribaye village. The analytical model used in this research is multiple linear regression. The results of the research show that the wage variable partially has a significant and positive effect on the amount of working time of female ketak woven craftsmen, the work experience variable partially has a significant and positive effect on the amount of working time of women ketak woven craftsmen, the variables are age, number of dependents, marital status, and the presence of toddlers. partially, it has no significant and negative effect on the amount of working time of women who make ketak woven crafts. The results of the research simultaneously show that the variables of wages, work experience, age, number of dependents, marital status and the presence of toddlers together have a positive and significant effect on the amount of work of female ketak woven craftsmen.